Morphological evaluation of aortic vessel in Spontaneously Hypertensive Rat (SHR) Models - Ramli, Nurul Syahida; Baharun, Bibi Nur Bazlini; Ismail, Azlini; Abu Bakar, Nor Hidayah; Noordin, Liza; Wan Ahmad, Wan Amir Nizam (Microscopy Society (Singapore), 2019)
The spontaneously hypertensive rat (SHR) has been well established as a suitable model for hypertension research, but little is known about the morphology of hypertensive vascular remodeling in this model. The present study was designed to investigate the structural changes of blood vessels in 6 months aged SHR in comparison to their corresponding model, Wistar Kyoto rats (WKY). The study utilised 12 male rats; which were equally divided into 6 SHR and 6 WKY. During dissection, thoracic aorta was harvested for histological examination. To evaluate the morphological appearance of SHR and WKY, hematoxylin and eosin (H&E) stain was done. Whereas Scanning electron microscopy was applied to view the ultrastructure of the vessel. The result shows that the aorta histology of WKY looks normal; depicted by showing smooth intima with a single layer of endothelial cells. In contrast with SHR, the structure was slightly distorted and thicker intima observed; suggesting vascular remodeling has occurred.